Microwave-assisted encapsulation of cyclodextrin metal-organic frameworks (γ-CDMOF-1) carrier for the delivery of quercetin and curcumin against lung cancer with improved release kinetics and molecular interaction analysis - Kenfack Tiofack, Saurelle; Kenfack Tsobnang, Patrice; Mohamad Latif, Muhammad Alif; Ngoune, Jean; Abdul Rahman, Mohd Basyaruddin (Elsevier, 2025)
Polyphenol compounds like quercetin (QE) and curcumin (CCM) have demonstrated good potential in killing lung cancer cells, but their low physicochemical stability and poor aqueous solubility hinder their use. Herein, this study presents the synthesis and characterization of γ-Cyclodextrin Metal-Organic Framework (γ-CDMOF-1), a promising drug delivery system and an improving agent of the aqueous solubility of these bioactive molecules. Powder X-ray diffraction and Fourier-transform infrared spectroscopy confirmed the synthesis of γ-CDMOF-1 and the drug loading. High-resolution transmission electron microscopy and Field emission scanning electron microscopy showed the cubic shape of unloaded and loaded γ-CDMOF-1. Atomic force microscopy showed decreasing roughness, confirming the encapsulation of curcumin and quercetin inside the γ-CDMOF-1. Brunauer–Emmett–Teller (BET) results revealed that the surface area of γ-CDMOF-1, CCM@CDMOF-1, and QE@CDMOF-1 samples are 809, 541, and 359 m2/g, respectively. Encapsulation efficiency and loading capacity of CCM in γ-CDMOF-1 at 1000 μg/mL are (43.57 ± 1.71) %, (53.41 ± 1.9) mg/g, respectively, while those of QE are (65.35 ± 1.78) %, (91.36 ± 3.12) mg/g, respectively. Curcumin and quercetin are released from CCM@CDMOF-1 and QE@CDMOF-1 at least three times than curcumin and quercetin in the PBS and SLF media at pH 6.0 and 7.4. The solubility of CCM and QE loaded in γ-CDMOF-1 increases, nearly 2180-fold and 113-fold more than pure curcumin and quercetin, respectively. The molecular docking simulations showed that CCM@CDMOF-1 and QE@CDMOF-1 have the binding affinity of −9.2 kcal/mol and − 8.6 kcal/mol, respectively. Hydrogen bonds are mainly involved in the formation of both composite materials. The encapsulation of curcumin and quercetin into the γ-CDMOF-1 through a microwave-assisted method in the range of 100 to 1000 μg/mL improves the drug delivery and the water solubility of these bioactive molecules.